Three new complexes based on methyl-pyrimidine-2-thione: in situ transformation, crystal structures and properties. Issue 20 (17th October 2016) - Song, Jiang-Feng; Jia, Ying-Ying; Shao, Jia; Zhou, Rui-Sha; Li, Si-Zhe; Zhang, Xiao
Abstract: Three complexes based on methyl-pyrimidine-2-thione, 5-methyl-5, 8, 9, 10-tetrahydro-5, 9methanopyrimido[5, 4-e][1, 3]diazocine-2, 7-dithiol (mtmdd) (1 ), and Ni(mpymt)2 (N2 H4 )·H2 O (2 ) and [Cd(mpymt)2 ]∞ (3 ) have been synthesized under hydrothermal conditions and characterized by elemental analysis, infrared (IR) spectroscopy, thermal gravimetric analysis, powder X-ray diffraction, and single-crystal X-ray diffraction. Structural analysis reveals that1 is generated from an in situ translation of mpymt. In2, two Ni(mpymt)2 fragments were joined into a dinuclear complex by two NH2 –NH2 molecules. Compound3 is a two-dimensional Cd coordination polymer constructed by Cd2 (mpymt)2 SBUs and mpymt anions. Variable-temperature magnetic susceptibility measurement of2 revealed strong antiferromagnetic interactions between nickel magnetic centers. The fluorescent properties of1 and3 were investigated in the solid state. Abstract :